2005
DOI: 10.1002/ptr.1663
|View full text |Cite
|
Sign up to set email alerts
|

Aged garlic extract improves endothelial function in men with coronary artery disease

Abstract: Endothelium-dependent vasodilation is impaired and predicts the risk of a coronary event in patients with coronary artery disease (CAD). Oxidant stress and increased systemic inflammation may contribute to this endothelial dysfunction. Aged garlic extract (AGE) contains antioxidant compounds and increases nitric oxide production and decreases the output of inflammatory cytokines from cultured cells. The aim of this study was to test the effect of treatment with AGE on brachial artery flow mediated endothelium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 31 publications
5
92
1
Order By: Relevance
“…The main outcomes of these studies consisted of BP, lipids profile, endothelial function, oxidative stress, inflammatory biomarkers, and coronary artery calcification (CAC), platelet aggregation and adhesion just as changes in 10 years prognostic risk of myocardial infarction and sudden death. Within lipids profile measured by the two interventions [38,39,40], LDLc and TC parameters were significantly decreased after allicor treatments [39]. Reduction of CAC progression was detected in the study that assessed it [38] (table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The main outcomes of these studies consisted of BP, lipids profile, endothelial function, oxidative stress, inflammatory biomarkers, and coronary artery calcification (CAC), platelet aggregation and adhesion just as changes in 10 years prognostic risk of myocardial infarction and sudden death. Within lipids profile measured by the two interventions [38,39,40], LDLc and TC parameters were significantly decreased after allicor treatments [39]. Reduction of CAC progression was detected in the study that assessed it [38] (table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Sobenin et al [39] observed a decrease in multifunctional prognostic risk of myocardial infarction and sudden death prevents the rise of risk with aging. Williams et al [40] only reported significant changes in the endothelial function. Ried et al [41] also assessed the effect of AGE in capsules (960 mg/day containing 2.4 mg S-allylcysteine), as well as of different doses (240/480/960 mg/day (0.6/1.2/2.4 mg/day of S-allylcysteine)) [42] as an adjuvant to antihypertensive medication in patients with uncontrolled hypertension, both during 12 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…112 Intravenous administration of Ginkgo biloba extract to patients with CAD increased LAD coronary artery blood flow and brachial artery flow-dependent dilatation. 113 In addition, plasma NO increased and ET-1 decreased after 2 weeks of ginkgo extract treatment; a linear correlation was obtained between the percentage change in LAD coronary artery blood flow and in NO, ET-1, or NO/ ET-1 ratio following extract treatment, suggesting that the ginkgo extract led to an increase in coronary blood flow, which may be related to improvement of NO/ET-1 imbalance.…”
Section: Herbal Agentsmentioning
confidence: 99%